The Effectiveness of Using the Think-Pair-Share Strategy in Teaching Arabic Writing Skills - Pardiyah Kunuza Amaliyah; Mawani Maswani; Fatima El Zahraa (Al-Muyassar: Journal of Arabic Education, 2025)
This research aims to explore the results of using the Think-Pair-Share strategy in teaching writing skills and to examine its effectiveness.The researcher used the quantitative method with a type of quasi-experimental design using the nonequivalent control group design. The sample was taken from classes 10-8 and 10-10, each consisting of 33 students. Class 10-10 was the experimental group using the Think-Pair-Share strategy, while class 10-8 served as the control group. The strategy was applied in writing instruction by presenting material through a projector and a workbook. Students understood the texts and vocabulary, then the teacher demonstrated how to arrange words into sentences and paragraphs before giving exercises. After that, the teacher provided questions based on the taught examples. Then, students answered individually (Think), discussed with a partner (Pair), and presented their answers in front of the class (Share).The results of this study proved that the Think-Pair-Share strategy was effective in teaching writing skills. This was evident from the increase in the post-test average score of the experimental group (77.66), which was higher than the control group's average score (58.81). Moreover, the Independent Sample T-Test results showed that the sig (2-tailed) value was 0.01, which was smaller than 0.05, meaning that the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. The N-Gain test result for the experimental group was 0.55, which, according to the N-Gain effectiveness standard, indicates a moderate level of effectiveness. Keywords: Effectiveness, Teaching Writing Skills, Think-Pair-Share. مستخلص البحثهد? هذا البحث إلى الكش? عن نتائج استخدام إستراتيجية ?كر-زاوج-شارك ?ي تعليم مهارة الكتابة، وكش? ?عالية استخدامها. استخدمت الباحثة ?ي هذا البحث المنهج الكمي مع نوع البحث ذو التصميم شبه التجريبي باستخدام تصميم مجموعة التحكم غير المكا?ئة (Nonequivalent Control Group Design). أخذت العينة من الص? العاشر - 8 والص? العاشر - 10. حيث تكوّن كل منهما من 33 طالبًا، عمل الص? العاشر - 10 ك?ئة تجريبية باستخدام إستراتيجية ?كر-زوج-شارك، والص? العاشر –8 كص? تحكم. طبقت الباحثة الإستراتيجية ?كر-زاوج-شارك ?ي تعليم الكتابة من خلال تقديم المادة عبر جهاز العرض والكتاب الإرشادي. ?هم التلاميذ النصوص والم?ردات، ثم عرض المعلم طريقة ترتيب الكلمات ?ي جمل و?قرات قبل أن أعطى التمارين. بعد ذلك، قدم المعلم أسئلة تستند إلى الأمثلة التي درّست من قبل. ثم أجاب التلاميذ على الأسئلة بشكل ?ردي (?كر)، ثم ناقشوها مع شريك (ناقش)، وأخيرًا قدموا الإجابات أمام الص? (شارك) .أثبتت نتائج هذا البحث أن إستراتيحية ?كر-زاوج-شارك ?ي تعليم مهارة الكتابة كانت ?عالة. ظهر ذلك من خلال زيادة متوسط درجة الاختبار البعدي للمجموعة التجريبية 77،6٦ والتي ?اقت متوسط درجة الإختبار البعدي للمجموعة الضابطة 58،81. علاوة على ذلك أظهرت نتائج اختبار-ت مستقل (Independent Sample T-Test) أن قيمة sig (۲ ذيل) 0،01 مما دلّ على أنها كانت أصغر من0،05 بحيث ال?رضية الص?رية (Ho) مر?وضة، وال?رضية البديلة (Ha) مقبولة. كانت نتيجة اختبار  "N-Gain "المجموعة التجريبية هي ٠،55 و?قا إلى معيار ?عالية  "N-Gain" هذه نتيجة على نسبة متوسطة. الكلمات الم?تاحية: ?عالية، تعليم مهارة الكتابة، ?كر-زاوج-شارك.